Pengembangan Video Singkat Screen Dependency Disorder Pada Anak Berbasis Perspektif Ibu - Sjamsuddin, Irfan Nafis (UI Scholars Hub, 2022)
Background. Childhood is a golden period of growth and development, as well as being vulnerable to negative influences. The use of digital devices has both positive and negative impacts. Screen Dependency Disorder (SDD) is a child development problem that needs to be prevented. Objectives. Knowing the mother's perspective on the duration of digital device use, and SDD in children, and developing an SDD short video based on the mother's perspective. Method. Design is development research. The population is mothers of children aged 1-13 years with a total of 68 people, the total sample. Preliminary research explored the characteristics of the respondents, the perspectives of respondents about the length of use of digital devices and SDD in children, by using a questionnaire in the Google form distributed via WhatsApp. Data were analyzed by frequency distribution, as well as the Sommers'd relationship test. The results form the basis for developing and designing short videos. Results. As many as 63.2% of children use digital devices for more than two hours per day. As many as 50% of mothers have a good perspective on SDD in children. There is a significant relationship between age-mother's occupation, age-education of children, family income with the duration of use of digital devices. There is no significant relationship between all the characteristics of the respondents with the SDD perspective. The short video developed contains understanding and prevention of SDD. Conclusion. Short videos can be used by testing it first. Advocacy is needed to gain support for SDD prevention efforts.